Penyebarluasan Media EXCOTION dalam Pembelajaran Biologi pada MGMP Biologi Kota Malang - Ramadhan, Muhamad Justitia; Kharomah, Sinta; Zahrah, Natasya Adiba; Kharomah, Sindi; Setiawan, Deny; Mahanal, Susriyati; Zubaidah, Siti (Universitas Nusantara PGRI Kediri, 2025)
Learning media needs to be developed to support the learning process. This community service program aims to disseminate game-based learning media “EXCOTION” to biology teachers in Malang City MGMP. This program is carried out with the stages of preparation, implementation, and evaluation. Based on the results of the analysis of the activity participant response questionnaire, the participants agreed with a percentage of 100%, that the learning media products and service activities had good benefits. Thus, this “EXCOTION ” media dissemination activity has provided benefits for biology teachers to be able to develop similar learning media so that students can overcome their difficulties in learning biological material, especially the excretory system in humans.